Quantitative gender analysis country report, Malawi: Building equitable climate resilient African bean and insect sectors - Kabuli, Hilda; Ouya, Frederick; Chisale, Virginia; Kachigamba, Donald; Feston, Chakhumbira; Sara, Botha; Lutomia, Cosmas; Ketema, Dessalegn; Nchanji, Eileen (Bioversity International and International Center for Tropical Agriculture, 2025)
This study presents findings from a quantitative gender analysis conducted in March 2025 under the Building Equitable Climate Resilient African Bean and Insect Sectors (BRAINS) project in Nkhotakota and Mwanza districts of Malawi. The assessment examined gender-differentiated participation, decision-making, and access to resources across three priority value chains—common beans, fruit trees (mango and avocado), and insects for food and feed—with the aim of informing inclusive, climate-resilient agricultural interventions. Data were collected from 201 randomly selected households using structured household questionnaires and analysed using gender-disaggregated descriptive and inferential statistics. The results reveal persistent gender inequalities that shape production potential, market engagement, and climate adaptation outcomes. Men generally have greater access to land, cultivate larger areas, adopt a wider range of improved bean and fruit varieties, and are more connected to extension services and formal market channels. Women, in contrast, operate on smaller plots, rely more on informal seed and market systems, and face constraints related to land tenure insecurity, lower mobile phone ownership, and limited access to technical and climate information. Within the bean value chain, men dominate decisions on crop choice and control over income from sales, while women are more engaged in subsistence production and local markets. Women show lower adoption of improved bean varieties and reduced access to higher-value buyers, despite their central role in household food provision. In fruit tree production, both women and men rely heavily on local varieties, but men are far more likely to grow improved mango and avocado varieties and to access more diverse marketing options. Decision-making on fruit sales and income remains concentrated with household heads, reinforcing gendered power imbalances. Knowledge and use of insects for food and feed are relatively high, particularly for termites and crickets, yet men consistently report higher awareness than women, especially regarding climate mitigation benefits. Participation in beekeeping is low overall and skewed toward men, who also receive more extension support. However, women who engage in beekeeping tend to invest more in modern hive technologies, suggesting strong potential returns to targeted support. Social capital analysis shows that women are more active in savings, credit, and welfare-oriented groups, while men dominate technical, administrative, and research-related groups. Access to agro-weather information services is high for both genders, largely through government channels, but men benefit more from formal institutional sources, whereas women rely more on informal and group-based networks. Overall, the findings demonstrate that gender inequalities persist across all examined value chains, limiting women’s ability to fully benefit from climate-resilient and nutrition-sensitive agricultural opportunities. At the same time, strong participation in social networks, widespread access to agro-weather information, and growing interest in diversified enterprises present clear entry points for gender-responsive programming. Addressing structural barriers to women’s access to land, information, extension services, and markets will be critical for enhancing productivity, improving food and nutrition security, and strengthening inclusive climate resilience under the BRAINS project.